Fading Characteristics in Evaporation Duct: Fade Margin for a Wireless Link in the South China Sea - Zaidi, K.S. (Institute of Electrical and Electronics Engineers Inc., 2018)
Evaporation ducts (ED), which are caused by a rapid decrease in the refractive index of the lower atmosphere, are known to trap radio waves between the evaporation duct layer and the sea surface. Although signal propagation and refractivity estimation in evaporation ducts have been well studied, the fading characteristics of ED must be accurately established to help determine fade margin, required for a reliable wireless communication link. In this paper, based on the percentage of occurrences of evaporation ducts, that have been measured and reported in the literature, the statistical distribution of path loss in the South China Sea is calculated for varying distances. These path loss distributions are weather-dependent and time-varying and define several slow time-varying fading characteristics. These slow fading characteristics are, what can be termed as log-lognormal in nature. Propagation in ED, being non-line-of-sight, also has a fast-fading component that is Rayleigh in nature. Once, the complete fading characteristics are known, the overall fade margin due in part; to both slow fading and fast fading can be obtained. For a distance of 100 km, approximately 99 availability can be obtained with an 88-dB fade margin while for a shorter distance of 50 km, the required total margin for 99 availability is only 50-dB. Â© 2013 IEEE.